Validación del procedimiento de Reclutamiento y Selección de Personal en la empresa Estación ASTRO, Santa Clara. - Meléndrez Soto, Zenia (Universidad Central "Marta Abreu" de Las Villas, 2010)
The present diploma work was carried out in the company Station ASTRO, Santa Clara. The same one has as general objective to validate the procedure designed for the recruitment and selection of personal in the department of RH, of the company Station ASTRO, Santa Clara. In the development of the investigation diverse tolos were used to diagnose the Managerial Improvement and the recruitment procedure and selection of personal, I eat for example: the analysis and synthesis, the work with the group of experts and the interview, among others. To give execution to the proposed general objective, a checkup list was designed with the aspects that refer mainly the NC 3001: 2007, the Ordinance 281 and the Resolution 8 of 2005 as for selection and integration. Subsequently this checkup list was validated, comparing the previously mentioned aspects and that specified in the recruitment procedure and selection of personal, with to the help of a group of experts and of the author of the present investigation and, lastly, the checkup list was validated for its generalization with the help of this same group of experts. The diagnosis of the procedure as well as their validation will contribute to the invigoration of the company through the contribution carried out by the author of the present investigation. All this pursues the purpose of achieving that the procedure is more comprehensive and contain in him all the necessary one to obtain bigger quality in the results and correspondence with that settled down in the effective labor legislation.
Keywords: Procedimiento de Reclutamiento; Selección de Personal; Perfeccionamiento Empresarial; NC 3001: 2007 y Decreto 281; Resolución 8 de 2005; Empresa Estación ASTRO, Santa Clara